Assessing precipitation event characteristics throughout North Carolina derived from GPM IMERG data products - Bartuska, Elizabeth; Beighley, R. Edward (Frontiers in Water, 2024)
The Global Precipitation Measurement (GPM) mission provides near-real time precipitation estimates that can be used for monitoring water supply infrastructure. To better understand the potential use of GPM data products for use in relevant applications, this study examines the performance of the Integrated Multi-satellitE Retrievals for GPM (IMERG) precipitation products throughout North Carolina to capture rainfall events. Event characteristics derived from IMERG precipitation products: early (4 hours latency), late (14 hours latency), and final (3.5 month latency) are compared to characteristics derived from gauges (N=282) for the period 2000-2021. Results show that the IMERG data products identify events reasonably well (mean event errors of 6.0 mm, 6.8 mm, and 1.7 mm for early, late and final products; probability of detection: 0.83, 0.83, 0.86; false alarm ratio: 0.20, 0.18, 0.18, respectively). While the final product performs best, the early and late products perform similarly. While additional research is needed to better understand factors leading to under- and over-estimates of event magnitudes, the findings from this study support the potential use of early/late IMERG data products in water supply monitoring or flood warning systems, where rapid estimates of event precipitation characteristics are needed.